The Institutionalization of Halal Certification in South Korea: Multidimensional Dynamics of Challenges and Opportunities - Moh Musyafak; Yang Dongcheol; Heri Akhmadi (Journal of social Philantrophy and Halal Research, 2024)
This study explores the institutionalization of halal certification in South Korea, highlighting social, regulatory, and certification body fragmentation challenges that impact the growth of the halal industry. Using a qualitative phenomenological approach, this research reveals local perceptions of the halal concept and the social barriers affecting the acceptance of halal products in the domestic market. The analysis shows that misunderstandings about halal and social resistance in South Korea slow the development of the domestic halal market. Additionally, the fragmentation of certification bodies with differing standards creates confusion within the industry and impedes the accessibility of halal products to international markets. Nonetheless, there are significant opportunities for South Korea to expand the halal sector through exports and Muslim-friendly tourism by addressing regulatory challenges and enhancing public education. The findings of this study provide strategic insights for the government and industry players to optimize the competitiveness of South Korean halal products in the global market